Medicago scutellata seed dormancy breaking by ultrasonic waves - Nazari, Meisam; Sharififar, Amin; Asghari, Hamid Reza (Plant Breeding and Seed Science, 2014)
In this study dormancy breaking of a hard-coated plant seed, Medicago scutellata, was investigated. The ultrasonic waves effect on the seed germination percentage, germination rate, radicle length and stalk length growth was assessed. Six treatments of waves exposure periods including 0, 1, 3, 5, 7, and 9 minutes were tested under laboratorial conditions. Statistical analyses were done at probability level of 0.01. Results revealed that the ultrasonic waves have a significantly positive effect on the seed dormancy breaking, but there was no linear correlation between the increasing times of exposure with any of the growth features. The best treatment for germination percentage and germination rate was the 7-minute one and the 3-minute one was the best for radicle length growth. Treatments of 3, 5 and 7 minutes had the same effect on stalk length growth and were better than all other treatments. The 9-minute treatment had a negative effect, even lessening the growth of all of the assessed features in comparison with the control treatment.